Variation in diet of the West coast rock lobster (Jasus Ialandii) : influence of rock-lobster sex, size and food environment - Atkinson, Lara Jane (Department of Biological Sciences, 2017)
Few studies of rock-lobster diet have included analyses of mature females or juveniles of either sex. This study focused on the diet of male and female West Coast rock lobsters (Jasus lalandii) in three size classes (viz.: 10 - 35 mm CL (carapace length) - small, 40 - 59 mm CL - medium and 70 - 85 mm CL - large), using visual analyses of stomach contents. The principle aims were to examine potential differences in diet between: (1) male and female rock lobsters; (2) changes in diet with size and (3) a comparison of rock-lobster diet between areas of known fast- and slow-growth rates. The primary prey items of rock lobsters are shown to be the black mussel (Choromytilus meridianalis), ribbed mussel (Aulacomya ater), barnacle (Notomegabalanus algicola), sea urchin (Parechinus angulosus), sponge and crustacean remains. There was no difference in diet between male and female rock lobsters within any size class. Bray-Curtis similarity dendograms and Multi-Dimensional scaling plots revealed differences between small, medium and large rock-lobster diets. Small rock lobsters consumed mainly ribbed and black mussels, whereas medium rock lobsters consumed higher percentages of barnacle and sponge. Sea urchins comprised a substantial percentage of large rock-lobster diet. ANOSIM (Primer v 4.0) established significant differences (p < 0.05) among diets of the three size classes. Differences in diet were also observed between areas of fast- and slow-growth rates, but these were limited to the small and medium size classes. Key prey items responsible for this difference in diet were black mussel and rock-lobster remains. The gut fullness index decreased with increasing rock-lobster size. In conclusion, there appears to be no difference in diet between male and female rock lobsters, regardless of their size. However, rock-lobster diet does appear to vary with size. The inverse relationship between gut fullness indices and size, suggests that small rock lobsters, which have a higher moult frequency, feed relatively more frequently than larger rock lobsters. Diet composition plays a role in determining the growth rate of rock lobsters from different areas.